1989
DOI: 10.1021/ja00208a038
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced destabilization of bilayer vesicles

Abstract: The polymerization of lipid bilayer vesicles (liposomes) is an effective method to enhance the long-term colloidal and chemical stability of the aqueous suspensions.1 A host of methods to polymerize vesicles have been described since the first reports in the early 1980s.2 It was soon recognized that the polymerization of two-component vesicles, where only one component was polymerizable, resulted in phase separation of the lipids into polymeric and monomeric domains.3"5 The polymerizable lipids form

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 1 publication
1
37
0
Order By: Relevance
“…Moreover, the targeting of liposomes to desirable sites has been attempted. 1,2) In addition, a number of attempts have been made to develop functional liposomes, which can regulate the release of drugs responding to various stimuli, such as pH, [3][4][5][6] light 7,8) and temperature. …”
mentioning
confidence: 99%
“…Moreover, the targeting of liposomes to desirable sites has been attempted. 1,2) In addition, a number of attempts have been made to develop functional liposomes, which can regulate the release of drugs responding to various stimuli, such as pH, [3][4][5][6] light 7,8) and temperature. …”
mentioning
confidence: 99%
“…Investigations by Papahadjopoulos and coworkers (Dalke et al, 1990) photocleavage of lipid chains (Kusumi et al, 1989;Anderson & Thompson, 1992b), photoinduced change in the association of polyelectrolytes with liposomes (You & Tirrell, 1991), and the photopolymerization of lipids (Frankel et al, 1989;Lamparski et al, 1992). These methods were generally designed for liposome lysis.…”
Section: Endocytosismentioning
confidence: 99%
“…The polymerization of bi-or mUlti-component liposomes has been usefully employed to form domains of enriched lipids for the insertion of transmembrane proteins into partially polymerized liposomes Tyminski et al, 1988), for the efficient photoinduced lysis of oligolamellar liposomes (Frankel et al, 1989;Lamparski et al, 1992), and for the enhancement of energy transfer between membrane surface bound dyes . In each of these cases the covalent linking of the polymerizable lipids separates the lipids into polymeric and monomeric domains (Gaub et al, 1984).…”
mentioning
confidence: 99%
“…Recently Frankel et al showed that if the nonpolymerizable component prefers a nonbilayer rather than a lamellar structure, the membrane will be destabilized. 24 Certain lipids, e.g. phosphatidylethanolamines (PE), are of particular interest because they form nonbilayer structures under physiological conditions.…”
Section: Conversion From Bilayer To Nonbilayer Supramolecular Structuresmentioning
confidence: 99%